Fabrication of Al7075 / B4C Surface Composite by Novel Friction Stir Processing (FSP) and Investigation on Wear Properties. (2016) - Rana, H.G.; Badheka, V.J.; Kumar, A.
Abstract: Friction stir processing (FSP), a process, derived from the friction stir welding (FSW) process, is an emerging novel, green and energy efficient processing technique to fabricate surface composite. In the present investigation, FSP technique has been used for fabrication of surface composites, using aluminium 7075 as parent metal and Boron Carbide (B4 C) powder particles as reinforcement., Aluminium 7075 has been selected as matrix phase, as being widely used by automotive and aerospace application and having the highest strength among all commercial Al alloys. In present paper, details about the fabrication of Al 7075-T651- B4 C surface composite for various combination of tool rotation, tool travel speed and number of passes have been discussed. The same being intended to improve hardness and thereby wear resistance. The fabricated surface composites are examined for microstructure using image analyser, and found friction stir processed zone with a few defects. It is also observed that the average hardness of friction stir processed surface composite was 40 – 70% higher than that of parent metal (75 – 80 HV). Wear Resistance is found to be improved by 100% compared to parent metal. The increase in same is attributed to B4 C particles dispersed in aluminium matrix and grain strengthening mechanism.